Perinatal risk factors for necrotizing enterocolitis. Issue 5 (May 1984) - Yu, V Y; Joseph, R; Bajuk, B; Orgill, A; Astbury, J
Abstract : The perinatal histories of 50 very low birthweight infants weighing 1500 g, or less, with necrotizing enterocolitis were compared with those of the remaining 325 very low birthweight infants who were admitted to this hospital during a four year study period. Many factors previously reported to be associated with necrotizing enterocolitis were found with equal frequency in both groups of babies. The only adverse factor which was more frequently present in patients with necrotizing enterocolitis was hypothermia on admission to hospital. Those infants who developed severe necrotizing enterocolitis also had a higher incidence of polycythaemia. A further controlled study which examined feeding practices showed that the timing, type, and volume of milk feeding were not different in infants with necrotizing enterocolitis and matched controls. Prematurity is clearly the greatest risk factor which predisposes to the development of necrotizing enterocolitis and most of the factors previously implicated in the aetiology may simply represent the descriptive characteristics of a population of sick, very low birthweight infants.